PERAN LINTAS SEKTOR DALAM KONVERGENSI PERCEPATAN PENURUNAN STUNTING DI KABUPATEN ROKAN HULU - Amir Syamsuadi; Ade Febriani; Ermayani Ermayani; Bubung Bunyamin; Nursyiamah Nursyiamah (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2023)
After being designated as a locus of stunting in Riau Province in 2017, Rokan Hulu Regency took various policy steps. This effort was actualized by the local government's efforts to build collaborative synergy between regional government apparatus organizations in a stunting integrated This study analyzes and describes the role of cross-sectors in the convergence of the acceleration of stunting reduction in Rokan Hulu district. The approach in this research is qualitative research in the form of field research by collecting primary and secondary data sources through in-depth interviews and document review. The results showed that the Government of Rokan Hulu Regency made efforts to reduce stunting in a structured and comprehensive manner, such as identifying the distribution of stunting, conducting program availability, and constraints in implementing integrated nutrition interventions, developing activity plans to improve the implementation of integrated nutrition interventions, holding stunting, providing certainty. laws for villages to carry out village roles and authorities in integrated nutrition interventions, ensure the availability and functioning of cadres who assist village governments in implementing integrated nutrition interventions at the village level, improve stunting and intervention coverage, measure growth and development of children under five and publish rates stunting review the performance of programs and activities related to stunting periodically. The obstacles in accelerating the reduction of stunting include time synchronization in the planning and implementation of the activities of each regional apparatus organization, the non-implementation of standard budget allocations for the significant acceleration of stunting reduction, and the not yet optimal management of accuracy and data quality in accelerating the reduction of stunting in Rokan Hulu Regency.